A comparative survey study on current prescribing trends in non-steroidal anti-inflammatory drugs among practitioners in private set up and tertiary care teaching rural hospital - Alamchandani, Ravi; Sattigeri, B. M.; Karelia, P. S. (International Journal of Research in Medical Sciences, 2017)
Background: The study was conducted to compare the current prescribing trends of Non-Steroidal Anti-inflammatory drugs (NSAIDS) among private practitioners and practitioners at tertiary care teaching rural hospital. Methods: The prospective survey study was carried out by obtaining response to feedback questionnaire related to use of NSAIDs from 25 private & 25 tertiary care practitioners. Results: NSAIDs use was routine amongst private (66%) and tertiary care (77.6%) practitioners. Preferences of tertiary care practitioners were paracetamol (36%), diclofenac (20%), aceclofenac (20%), ibuprofen (20%) and etoricoxib (4%) while that of private practitioners were ibuprofen (40%), paracetamol (32%), diclofenac (16%) and aceclofenac (12%). Use of Fixed Dose Combinations (FDC) was 72% in private and 68% in tertiary care practitioners. While prescribing FDCs, private practitioners preferred NSAIDs + NSAIDs (100%) over NSAIDs + muscle relaxants (44.44%), NSAIDs + Serratiopeptidase (55.56%), and NSAIDs + antacids (44.44%) similarly tertiary care practitioners also preferred NSAIDs + NSAIDs (100%) over NSAIDs + muscle relaxants (47.06%), NSAIDs + Serratiopeptidase (36%), and NSAIDs + antacids (28%). Of the NSAIDs + NSAIDs combination ibuprofen + paracetamol (70%) was preferred by private practitioners and diclofenac + paracetamol (61%) by tertiary practitioners. Paracetamol was safely used during pregnancy by both groups. Adverse effects observed included gastritis (98%), urticaria (32%), and anaphylaxis (2%), although no fatality was observed. Conclusion: Not much of a difference was observed in prescribing habits of both groups. Though beneficial and routinely prescribed, NSAIDs with equal risk potential were observed to be cautiously used with appropriate knowledge amongst both the groups.